Crime-Related scenarios do not lead to superior memory performance in the survival processing paradigm. Issue 3 (3rd April 2022) - Mangiulli, Ivan; Hover, Nathalie; Howe, Mark L.; Otgaar, Henry
ABSTRACT: Processing information according to its survival value improves memory retention. We used mass-testing across three experiments to examine whether the survival processing advantage could be extended to crime-related contexts when adopting both offender's (Experiment 1 and 2) and victim's (Experiment 3) perspectives. Interestingly, crime-related scenarios produced the lowest memory retention in Experiments 2 and 3, indicating no mnemonic benefit resulting from crime-related processing. Furthermore, in Experiments 1 and 2, we failed to replicate the standard survival processing effect, while in Experiment 3 the superior survival memory retention emerged in comparison with the standard control conditions (i.e., moving and pleasantness). Overall, our experiments showed that crime-related contexts did not lead to superior memory retention. Moreover, although we detected some failures to replicate the survival processing effect, this evidence is not sufficiently compelling to argue that there was a general absence of the survival processing advantage.